Bacterial survival in the hostile environment a volume in developments in applied microbiology and biotechnology - Kumar, Ashutosh; Tenguria, Shivendra (Academic Press, 2022)
"Variety of bacteria are present in our environment but only a few of these bacteria causes diseases in their hosts including humans. These bacteria face different stresses in the environment as well as inside the host and adapt number of strategies for their survival. In 5 parts Bacterial Survival in the Hostile Environment covers all tactics and strategies adopted by bacteria for their survival under stressed conditions and will be focused on mechanistic insights of pathogenic adaptations to host environments (acidic environment, microaerobic conditions, immune system stress, metal stress etc., modulation of host pathways by pathogens for survival, dormancy, drug tolerance and resistance, proteins for stress survival). The content also includes different adaptation mechanisms of extremophiles to extreme environment, provides a complete and globally available advance knowledge related to bacterial survival from different perspectives and reviews the knowledge gaps and future prospects in the field of microbial adaptation for sustainable development of in the field of infection biology and pharmaceutics."